Differentiating parametric design: Digital workflows in contemporary architecture and construction. (September 2017) - Wortmann, Thomas; Tunçer, Bige
Abstract : This paper examines Parametric Design (PD) in contemporary architectural practice. It considers three case studies: The Future of Us pavilion, the Louvre Abu Dhabi and the Morpheus Hotel. The case studies illustrate how, compared to non-parametrically and older parametrically designed projects, PD is employed to generate, document and fabricate designs with a greater level of detail and differentiation, often at the level of individual building components. We argue that such differentiation cannot be achieved with conventional Building Information Modelling and without customizing existing software. We compare the case studies' PD approaches (objected-oriented programming, functional programming, visual programming and distributed visual programming) and decomposition, algorithms and data structures as crucial factors for the practical viability of complex parametric models and as key aspects of PD thinking. Highlights: Presents case studies of Parametric Design (PD) in current architectural practice. PD for generation, documentation, fabrication and assembly of differentiated designs. Compares objected-oriented, functional, visual and distributed visual PD approaches. Decomposition, algorithms and data structures are crucial factors for PD in practice.